Polo para el desarrollo de la industria cultural de Cundinamarca y el fomento de la diversidad artística de la región “la cuarta pared” (2018)
The project to be developed will have an arduous study on its form, implementation, zoning and concept that will allow it to be solved in the best way possible and how it becomes a pole for the improvement of the region. In this part, the steps by which it was thought, developed and created a comprehensive urban, architectural and constructive plan that will allow the development of a project in the Bosa sector for the community and the region, will be explained from beginning to end. Concise and structured analysis can solve one of the most important problems in the region, such as violence and all its possible long-term consequences. Finally, all the necessary information to build the project in the space, such as the structure, the cuts, facades, evacuation plants and other planimetry that will allow understanding the space as a real place in the environment, will be deeply structured.